Short Communication: Insulin-like growth factor 1 (IGF-1) gene polymorphisms in Madura karapan and beef cattle breed - Dyah Perwitasari-Farajallah; ROSE IDA UMMAH; REVA ADZANI NURJANNAH; ACHMAD FARAJALLAH (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Perwitasari D, Ummah RI, Nurjannah RA, Farajallah A. 2019. Short Communication: Insulin-like growth factor 1 (IGF-1) gene polymorphisms in Madura karapan and beef cattle breed. Biodiversitas 20: 3070-3074. Madura cattle breed is one of the four existing indigenous cattle breeds (Aceh, Pesisir, Madura, and Bali) in Indonesia. This Indonesian breed derived from crossbreeding between Bos indicus (zebu) and Bos javanicus (banteng). Cattle raising in Madura focused on three purposes i.e. bull race competition (karapan), beauty contest (sonok) and meat production. Insulin-like Growth Factor 1 (somatomedin-IGF-1) is a protein that plays a key role in cell differentiation, embryogenesis, growth, and regulation of metabolism. In cattle, the IGF-1 gene was localized on chromosome 5. Due to their role in the regulation of cell proliferation and animal growth, the IGF-1 and its gene are considered as candidate markers for growth rate and meat production traits. This research aimed to determine nucleotide variations in the IGF-1 gene among Madura karapan and beef cattle. PCR amplification of IGF-1 gene was conducted using a pair of primers. Amplicon was sent to commercial DNA sequencing company (1st Base) to perform DNA sequencing analysis. The size of IGF-1 gene was approximately 762 bp consisted of intron 3, exon 4, and intron 4. Sequence data were analyzed using MEGA 7 to identify the presence of nucleotide variation. Bos indicus (NC032654) was used as a reference sequence. The results showed no polymorphism was observed in intron 3 and exon 4 of Madura karapan and beef cattle breed. We determined G491A point mutation in intron 4. In conclusion, IGF-1 could not be able to be used as a genetic marker to differentiate karapan and beef cattle and furthermore morphological characteristics still can be applied as a standard for selection.